ROZWÓJ KOMPETENCJI DYSKURSYWNEJ: EWALUACJA EFEKTÓW JEJ KSZTAŁCENIA - Pędzisz, Joanna (Neofilolog, 2019)
Developing students’ discourse competence: evaluation of a course. The purpose of this paper is to investigate the concept of discourse competence. The major part of the paper will be occupied by a summary of the findings of a qualitative study into the perceptions of discourse competence and ways it was developed with students of applied linguistics at the Maria Curie-Skłodowska University in Lublin (UMCS).